2021
DOI: 10.1016/j.devcel.2021.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast dedifferentiation as a determinant of successful regeneration

Abstract: Highlights d Fibroblast-derived Prrx1 + cells are the main constituent of a frog limb blastema d Frog fibroblasts only undergo partial dedifferentiation due to intrinsic limitations d Adult chondrogenesis is distinct from the embryonic program

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(141 citation statements)
references
References 47 publications
9
116
0
Order By: Relevance
“…Meanwhile, the second possibility would indicate establishing new gene regulatory networks that are not observed during development and potentially exhibit new functions. Based on the latest single-cell transcriptomics results from different species ( Xenopus [ 45 , 88 ], mouse [ 21 ] and the axolotl [ 80 ]), specific fibroblast cells express genes associated with blastema and show transcriptional programmes that are not seen during limb development. More specifically, in froglets, amputation was shown to induce a subset of fibroblasts to initiate a chondrogenic transcriptional programme that is different than the chondrogenic programme during limb development [ 88 ].…”
Section: Stem and Progenitor Cell Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the second possibility would indicate establishing new gene regulatory networks that are not observed during development and potentially exhibit new functions. Based on the latest single-cell transcriptomics results from different species ( Xenopus [ 45 , 88 ], mouse [ 21 ] and the axolotl [ 80 ]), specific fibroblast cells express genes associated with blastema and show transcriptional programmes that are not seen during limb development. More specifically, in froglets, amputation was shown to induce a subset of fibroblasts to initiate a chondrogenic transcriptional programme that is different than the chondrogenic programme during limb development [ 88 ].…”
Section: Stem and Progenitor Cell Typesmentioning
confidence: 99%
“…Based on the latest single-cell transcriptomics results from different species ( Xenopus [ 45 , 88 ], mouse [ 21 ] and the axolotl [ 80 ]), specific fibroblast cells express genes associated with blastema and show transcriptional programmes that are not seen during limb development. More specifically, in froglets, amputation was shown to induce a subset of fibroblasts to initiate a chondrogenic transcriptional programme that is different than the chondrogenic programme during limb development [ 88 ]. Hence, the previous terminology labelling so-called dedifferentiated cells could be indicating an injury-induced cell state for some fibroblast cell types rather than resetting to a developmental cell state.…”
Section: Stem and Progenitor Cell Typesmentioning
confidence: 99%
“…By performing transplantation and cell-fate tracing using chimeric froglets that have GFP-negative skin and GFP-labeled subcutaneous fascial tissues, Otsuka-Yamaguchi and colleagues found that subcutaneous fascial cells became blastema-like cells with activated Prrx1 limb enhancer, and contributed to regenerating the skin, especially the dermis, after an excision injury [84]. Recently, Prrx1 + fibroblasts have been shown to be responsible for scar formation of the ventral skin in mice [85], but a determinant of a successful limb regeneration in Xenopus laevis [86]. Therefore, understanding the key similarities and differences in fascial fibroblasts between mammals and lower vertebrates may provide molecular and cellular insights into scarless wound healing.…”
Section: Fibrotic Outcomes Of Fascia Repairmentioning
confidence: 99%
“…In addition to the cells’ differentiation, de-differentiation has also been involved in repairing cell stress, and is mediated by the EMT or MET [ 3 , 73 ]. Such processes can be easily found in the transition of myofibroblasts and fibroblasts [ 25 ]. Multiple cell resources have been identified to be able to transform into myofibroblasts under cell stress or injury.…”
Section: Differentiation and De-differentiation Between Emt And Metmentioning
confidence: 99%
“…Additionally, a similar processes of EMT can be observed when internal organ damage occurs [ 23 ], and some epithelium undergoes trans-differentiation to repair the damaged part [ 24 ]. When tissues are wounded, these phenomena can easily be observed in the whole body or on the skin or body surface, where epithelial trans-differentiation into mesenchymal cells with cell mobility occurs [ 25 ]. Mesenchymal cells come to the wound region to form an intact barrier and transform into epithelial cells during the “wound healing process” [ 26 ].…”
Section: Introductionmentioning
confidence: 99%